2019
DOI: 10.1108/ijqrm-09-2018-0233
|View full text |Cite
|
Sign up to set email alerts
|

Implications of TQM in firm’s innovation capability

Abstract: Purpose Over the last few decades, some researchers have analysed the role of total quality management (TQM) as a precursor of innovation. However, the relationship between TQM and organisational innovation remains unclear and contradictory. The purpose of this paper is to provide a framework intended to clarify the complex effect that the implementation of a TQM system has on organisational innovation, where market orientation (MO) and knowledge management (KM) play a mediator role. Design/methodology/appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 130 publications
(131 reference statements)
4
28
0
1
Order By: Relevance
“…Our findings are in line with previous studies that elicit the positive impact of quality practices on performance (Asif, 2019;Shokri and Nabhani, 2019;Basu et al, 2020;Jim enez-Jim enez et al, 2020). This is an important finding and provides empirical support from a global perspective.…”
Section: Theoretical Contributionssupporting
confidence: 92%
“…Our findings are in line with previous studies that elicit the positive impact of quality practices on performance (Asif, 2019;Shokri and Nabhani, 2019;Basu et al, 2020;Jim enez-Jim enez et al, 2020). This is an important finding and provides empirical support from a global perspective.…”
Section: Theoretical Contributionssupporting
confidence: 92%
“…The results of the current research showing a significant support for the second set of hypotheses reinforce the theoretical perspective of knowledge-based view that manufacturers leverage knowledge resources and internal competencies to enhance their ability to be market responsive resulting in improving firm's OP. As very little research exists directly relating PQM toward building firm's AC, the current study complements several research studies that highlighted the role of PQM in building the individual dimensions of OL (Tortorella et al, 2020), KM (Abbas, 2020) and IC (Jim enez-Jim enez et al, 2020). Thus, the results in the current research extends support to the third set of hypotheses that strengthen the practitioner's understanding of the importance of PQM in manufacturing firms and their role in enhancing knowledge-driven absorptive capabilities for realizing superior performance.…”
Section: Discussionsupporting
confidence: 64%
“…This is certainly relevant with the increased uncertainty of a volatile marketplace, where it is more impossible to discern what competitors are doing to gain their knowledge and to apply it to new products and processes (Albort-Morant et al, 2018;Xie et al, 2018). Supporting above discussions, several scholars in the OM research concluded that the adoption of PQM can only increase the OP of firms to a certain degree, emphasizing that the effectiveness of PQM on OP depends on several dimensions of the firm's absorption capability, such as organizational learning (Akg€ un et al, 2014;Tortorella et al, 2020), knowledge management (Abbas, 2020;Jim enez-Jim enez et al, 2020) and innovation capability (Akg€ un et al, 2014;Sahoo, 2019). These research studies have shown that the mentioned three dimensions of AC of the organization have more indirect impact than direct ones on operational productivity parameters, indicating their mediating roles.…”
Section: Pqm and Firm's Absorptive Capacitymentioning
confidence: 94%
See 2 more Smart Citations